Ø¯Ø±Ø§Ø³Ø© Ù…Ù‚Ø§Ø±Ù†Ø© Ø¹Ù† Ø§Ù„ÙØªÙˆÙ‰ Ø§Ù„Ù…Ø¹Ø§ØµØ±Ø© Ø¨ÙŠÙ† Ø¥Ù†Ø¯ÙˆÙ†Ø³ÙŠØ§ ÙˆÙ…Ø§Ù„ÙŠØ²ÙŠØ§ - Qonytha, Didin (Jurisdictie: Jurnal Hukum dan Syariah, 2014)
The discussion in this paper are the polemics of misyÃ¢r marriage that developed in the Bay State. This marriage is a marriage where a spouse has waived such right answer or do not earn a living and residence. The purpose to make the wedding the husband is free from obligation toward his wife to provide a living and residence as another wife. "discount" is only available for couples who are mostly his wife comes from a rich family and takes the figure of man as a social status. This study uses empirical methods qualitative comparison of the thinking approach with Indonesia and Malaysia Shariah lecture. The analysis results can be known that many of the informants who approved this marriage due to fulfillment a marriage license and the willingness of the wife without any coercion from any party. While some informants do not agree to give the reason that marriage is denying the essence of marriage i.e. form a family of sakinah, mawadah and rahmah.Pembahasan dalam tulisan ini adalah polemik nikah misyÃ¢r yang berkembang di Negara teluk. Tujuan pernikahan ini adalah agar suami bebas dari kewajiban terhadap istrinya untuk memberikan nafkah dan tempat tinggal seperti istri yang lain. â€œdiskonâ€ ini hanya diperoleh bagi pasangan yang sebagian besar istrinya berasal dari keluarga kaya dan membutuhkan sosok lelaki sebagai status sosial di kalanganya. Penelitian ini menggunakan metode empiris kualitatif dengan pendekatan perbandingan pemikiran dosen syariâ€™ah Indonesia dan Malaysia. Dari hasil analisis dapat diketahui bahwa banyak dari informan yang menyetujui pernikahan ini dikarenakan terpenuhinya rukun nikah dan kesediaan istri tanpa adanya pemaksaan dari pihak manapun. Sedangkan beberapa informan yang tidak menyetujui memberi alasan bahwa pernikahan ini mengingkari esensi pernikahanya itu membentuk keluarga sakinah, mawadah dan rahmah.